2014
DOI: 10.1080/02255189.2014.876390
|View full text |Cite
|
Sign up to set email alerts
|

Collecting high frequency panel data in Africa using mobile phone interviews

Abstract: As mobile phone ownership rates have risen in Africa, there is increased interest in using mobile telephony as a data collection platform. This paper draws on two pilot projects that use mobile phone interviews for data collection in Tanzania and South Sudan. In both cases, high frequency panel data have been collected on a wide range of topics in a manner that is cost effective, flexible and rapid. Attrition has been problematic in both surveys, but can be are explained by the resource and organisational cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…In two surveys that did not contain a control arm (ie, no incentive), there was either no discernible effect between the low and high incentive amount on response rates [18], or the higher incentive arm had lower response rate as compared with the lower incentive arm [14]. In Peru and Honduras, panelists were randomized to one of the following three arms: (1) no incentive, (2) US $1 airtime, and (3) US $5 airtime [13].…”
Section: Resultsmentioning
confidence: 99%
“…In two surveys that did not contain a control arm (ie, no incentive), there was either no discernible effect between the low and high incentive amount on response rates [18], or the higher incentive arm had lower response rate as compared with the lower incentive arm [14]. In Peru and Honduras, panelists were randomized to one of the following three arms: (1) no incentive, (2) US $1 airtime, and (3) US $5 airtime [13].…”
Section: Resultsmentioning
confidence: 99%
“…Remote forms of data collection, such as mobile and fixed-line phone surveys, are particularly effective in two contexts: i) settings where it is not safe or possible to perform face-to-face surveys, and ii) settings needing high-frequency data collection (Hoogeveen et al, 2014). Both settings are prevalent in MENA.…”
Section: Methodsmentioning
confidence: 99%
“…This was made even more evident when we asked for cell phone numbers. While the collection of phone numbers is now fairly standard practice in many data collection efforts in Africa (Hoogeveen et al 2014) and the use of mobile phones is ubiquitous in Kenya (KDHS 2014 reported 84% of households owned a mobile phone), it is not without challenges. About 90% of respondents provided their own phone number.…”
Section: Study Site Data and Methodsmentioning
confidence: 99%